Death, power, and apotheosis in ancient Egypt : the Old and Middle Kingdoms - Troche, Julia (Cornell scholarship online, 2022)
'Death, Power, and Apotheosis in Ancient Egypt' considers how power was constructed, maintained, and challenged in ancient Egypt through mortuary culture and apotheosis, or how certain dead in ancient Egypt became gods. Rather than focus on the imagined afterlife and its preparation, Julia Troche provides a novel treatment of mortuary culture exploring how the dead were mobilized to negotiate social, religious, and political capital in ancient Egypt before the New Kingdom